Unemployment and Bank Performance: The Moderating Role of Gross National Income per Capita - Hussain, Muhammad Mazhar; Zuhri, Elegı (International Journal of Economics and Financial Issues, 2025)
This study examines unemployment’s impact on Turkish bank performance, emphasizing gross national income (GNI) per capita’s moderating role. Analyzing 50 major Turkish banks (2013-2024) using panel data regression techniques like OLS, Fixed Effects Model, and Random Effects Model, with two-step Systems GMM robustness testing. Results demonstrate unemployment significantly and negatively affect both ROA and ROE, confirming that rising unemployment deteriorates bank profitability through increased credit risk and reduced loan demand. GNI per capita shows positive direct effects on bank performance, indicating higher national income levels enhance banking sector resilience. The unemployment-GNI per capita interaction reveals significant positive moderating effects, suggesting banks in higher-income environments better absorb unemployment shocks due to stronger household balance sheets and robust institutional frameworks. Control variables demonstrate expected relationships: cost-to-income ratio and leverage negatively correlate with profitability, while bank size and GDP growth show positive associations. These empirical findings provide valuable insights for policymakers, bank managers, and regulators designing targeted interventions considering labor market dynamics and income-level effects to enhance banking stability in middle-income emerging economies.